The Relationship Between Human Capital, Social Capital And Firm Growth Of Small Enterprises In Sri Lanka - Nishantha, B. (My University, 2011)
This study examined the effect of entrepreneur’s human capital and social capital on the growth of small enterprises (SEs) in Sri Lanka. The research study seeks to accomplish this examination by proposing a conceptual model of SE growth by using sales growth rate as an outcome variable. The data have been collected from 97 manufacturing enterprises that employ less than 50 employees in Colombo district of Sri Lanka. The hypotheses derived from human capital and social capital theories were tested in order to assess the relationship among human capital, social capital and the small enterprise growth. However, unlike previous research, the study gives specific consideration to how the relationship between human capital and small enterprise growth is moderated by social capital. The findings of the study suggest that human capital variables namely, training with work experience in same field , technical & professional education and education with experience in government sector have positive effect on sales growth trough social capital variable namely , organizational network with network maintenance. The research also highlighted the direct and indirect effect of training with work experience in same field on sales growth. Implications and directions for future research were discussed.